Asymptotically and Statistically Equivalent Functions Defined on Amenable Semigroups: Fatih Nuray, B.E. Rhoades - Team, Support (Thai Journal of Mathematics, 2013)
In this study we define the notions of asymptotically, statistically, almost statistically and strong almost asymptotically equivalent functions defined on discrete countable amenable semigroups. In addition to these definitions, we give some inclusion theorems. Also we prove that the strong almost asymptotically equivalence of the functions f(g) and h(g) defined on discrete countable amenable semigroups does not depend on the particular choice of the Folner sequence.